Scenarios of Nursing Organization in Private International Medical Hubs During 2022-2026 - Thuekun, Punyisa; Wisesrith, Wasinee (Journal of The Royal Thai Army Nurses, 2020)
The objective of this study was to examine the scenarios of nursing organization as a private international medical hubs during 2022–2026 through the Ethnographic Delphi Futures Research (EDFR) technique. The sample was composed of 18 experts. The research methodology was divided into the following three rounds. In Round 1, the researcher interviewed the experts for opinions concerning the scenarios of nursing organization as a private international medical hubs 2022–2026. In Round 2, the researcher used the data obtained from the interviews in content analysis and created a questionnaire for experts to estimate significant trends. And in Round 3, the researcher used the data obtained from Round 2 to calculate the median and interquartile range for preparation of the questionnaire for experts to confirm opinions and for the researcher to summarize the study. The summary of the results regarding the scenarios nursing organization as a private international medical hubs during 2022–2026 consisted of the following six items: 1) Nursing organizational structure; 2) Development and human resource management; 3) Innovation and technology; 4) Nursing service; 5) Strategic nursing management and 6) Excellent quality of service.